Konsep teologi Muhammad Abduh dan gerakan pembaharuannya dalam pendidikan Islam - Ulhaq, Muhammad Zhiya (Maliki Interdisciplinary Journal, 2024)
Islamic theology is the concept of divinity and divine values in the Islamic religion. One of the Islamic reformers and Islamic theologians, Muhammad Abduh, has the view that reason is the most important thing in religious life. Previously, the opinion of the textualists or jabariyah that everything was something that had been ordained by Allah and that there was no human intervention in it resulted in the narrow thinking of this group making Islam, which was once glorious and even called the golden age of Islam, decline drastically and even stagnate because Muslims were reluctant to think and like follow something that has been initiated. Every era has its own problems, so Abduh tried to completely erode the understanding of Jabariyah by making people aware of the importance of using reason as a medium of understanding and reasoning so that it is hoped that it will be able to revive the Islamic fighting spirit in fighting for Islam itself. When someone is intellectual, they also need to be accompanied by spiritual means to become a person with a big soul and noble morals. Muhammad Abduh concentrates on reconstructing the goals of Islamic education, which has many shortcomings, one of which is the memorization method because the memorization method is not accompanied by methods of understanding and reasoning, which makes students not understand and hate the lesson because they do not understand what they are learning.